SDFunc: Modular spreadsheet design with sheet‐defined functions in Microsoft Excel. (12th September 2021) - Turk, Tomaž
Abstract: The goal of the SDFunc tool is to enable spreadsheet developers to build their model computations in Microsoft Excel according to the modular design approach, that is, the separation of the functionalities into independent, interchangeable modules with interfaces that provide input and output elements. This concept has been theoretically developed in recent years and is known as sheet‐defined functions in the literature. In this article, we are presenting our implementation of the tool and the evaluation steps that we took to make the tool interesting and suitable for the assessment of the modular approach in spreadsheet development by the industry, specifically within organizational and companies' settings where the spreadsheet developers and end‐users involved in experiments expect to use a well‐established spreadsheet platform. We also demonstrated that sheet‐defined functions can be implemented by development tools already present in Microsoft Excel.